Caso de estudio: exportación de mermelada de papaya andina a Canadá - Pizarro Delgado, Alvaro Gonzalo (2019)
The following case study has been created in order to export marmalade of mountain papaya (Vasconcellea pubescens) due to its organoleptic properties, high nutritional value, unique taste and particular scent which makes a product very hard to imitate. This product is intended to compete abroad, specifically in the Canadian market, as a result it is necessary to define processes and strategies that optimizes a sustainable project and also to develop the brand of the product. Consequently, the company will leverage the potential of the target market. For all these reasons, this case gather qualitative and quantitative information, forecasts, and statistic data of the market, also a detailed analysis of the Canadian consumer and their current tendencies. Subsequently, it was defined a segment with a potential demand which is a critical point to elaborate and reach feasible results. That way it was conducted an exhaustive investigation of the chain of production which was defined by doing a study of related topics to Business Process Management, collecting data of secondary sources and other countries. Finally, it was designed a complete analysis of the chain of supply, including export costs. All these data was also collected out of primary and secondary sources of information. As a result of the investigation it was concluded that a proper and efficient coordination in every stage of the logistic process will determine how much return is being taken from the comparative advantage of the product, while the distribution of the resources of the company will be a conditioning factor, independently of the promotion and marketing efforts which are merely mechanism of market penetration in the first year, but in the mid-term they will be decisive to diversify the strategies of market detection or to explore new opportunities in the long run.